Respuesta :
Answer:
The answer to your question is y = x - 23
Step-by-step explanation:
Process
1.- Get the slope of the line
If two lines are parallels, it means that they have the same slope.
y = 1x - 10
Slope = m = 1
2.- Get the equation of the line
y - y1 = m(x - x1)
y + 29 = 1(x + 6) Substitution
y + 29 = x + 6 Expanding
y = x + 6 - 29 Simplifying
y = x - 23
Answer:
y = x - 23
Step-by-step explanation:
All lines parallel to the given line y = x - 10 have the same slope (1), and the same form of equaiton: y = x + C, where C is a constant.
We know that the new line passes through (-6, -29). Replacing x with -6, y with -29, we get:
-29 = -6 + C, and thus we find that C = -23.
Thus, the desired equation is
y = x - 23